Why Companies Default in Pakistan? Empirical Evidence from Textile Sector - Gillani, Syed Muhammad Ahmad Hassan; Raza, Hamad; Ahmad, Humara; Siddique, Muhammad (The journal of contemporary issues in business and government, 2021)
Bankruptcy or default is most undesirable satiation in companies’ life. Managers and researchers always looking for to find out factors which lead companies towards default. This study focuses on multilevel variables (firm, sector and county) and found on which level of variables are more important factor for causing default. This study used data from 41 non-financial textile firms 25 non-defaulted and 16 defaulted firms listed in PSX for 10 years from 2009 to 2018. Logistic regression and artificial nested testing procedure are employed to find our result. According to finding textile, firm level factors are most significant factors behind financial distress and defaults. For instance, profitability, activity, ownership concentration and chairman duality are main factors. Whereas none of sector level variables and country level variables are reported significant in defaults. As far as multi-level variables are concern, firms’ level are most influential factors for on financial health and performance of companies followed by sector level and country level variables. This study recommends that in future, under developing countries like Pakistan there are also many county level governance related variables e.g. like role of law, control of corruption and political instability may also affect companies performance and cause financial distress and default. Therefore, in future these variables may be incorporate with logit or other computer base tools like artificial neural networks.